Investigating morphological effects of estuarine channel branching on saline water intrusion: a case study of Modaomen Estuary - Wang, Pu; Hong, Liang; Lin, Juli; Liang, Hongyue; Li, Haiwei; Tan, Chao; Chen, Hui; Liu, Feng (Frontiers in Marine Science, 2025)
Within the context of global change, morphological evolution in estuary regions and the related effects on water resource safety are key concerns for the sustainable management of river deltas. Channel branching controls the morphological evolution patterns and sedimentary regime in river deltas and generally occurs in response to natural conditions and human activities. In this study, we focused on the impacts of channel branching on saline water intrusion in the Modaomen Estuary in China. The riverine discharge through the Modaomen Estuary supplies freshwater source for the Guangdong- Hong Kong- Macao Greater Bay Area; and morphological evolution greatly affects saline water intrusion in this region, posing a threat to freshwater security. In this study, we constructed an idealized model with a prototype of Modaomen Estuary while considering single and double channels, to explore the impacts of channel branching on saline water intrusion in estuaries. The results indicated that channel branching greatly influenced the morphological structure of the mouth bar in the estuary. The magnitude of saline water intrusion occurred more significantly during the neap tide than spring tide in both the single- and double-channel simulations. Channel branching exhibited different effects on the saline water intrusion during the spring and neap tides, by affecting the estuarine dynamics and circulation. Furthermore, the mouth bar exerted a ‘blocking effect’ on the intrusion and recession of saline water. Overall, our study presents scientific guidelines for estuarine regulation projects to ensure water resource safety and promote effective estuarine management.